Pendidikan Islam tentang Mistikasi Hantu Legend di Indonesia - Salis Irvan Fuadi; Robingun Suyud El Syam; Laila Ngindana Zulfa (La-Tahzan: Jurnal Pendidikan Islam, 2026)
Amid the widespread public belief in mystical phenomena and legendary ghosts, an Islamic perspective-based study is important to provide an understanding that aligns with the values of Islamic creed. This article aims to reveal the mystification of legendary ghosts in Indonesia from the perspective of Islamic education, a topic that has not been discussed in previous studies. This paper is the result of a literature research using a descriptive qualitative approach referring to relevant literature and analyzed descriptively. The research findings show that ghosts are part of devils that disturb humans, not the spirits of deceased people, but manifestations of devils resembling human figures or other forms. Devils are supernatural beings created by Allah with the mission of misleading humans by disturbing, slandering, and deceiving them. The existence of supernatural beings such as jinn and devils is something Muslims must believe in because they are mentioned in the Qur’an; denying them means denying the essence of the holy scripture itself. These findings highlight the religious aspect as the foundation of belief, transcending the limitations of human logic. This research also provides direction for future studies that emphasize religiosity as an approach to understanding supernatural phenomena based on scriptural sources in comprehending the unseen world.